Bismuth vanadate / biomass charcoal composite photocatalyst as well as preparation method and application thereof

By constructing a hetero-bound composite photocatalyst with biomass charcoal and bismuth vanadate, the problem of insufficient stability and adsorption capacity of BiVO4 photocatalyst in actual applications is solved, and the effect of efficient removal of antibiotics in water bodies is achieved, and the stable performance is maintained for a long time.

CN119857478APending Publication Date: 2025-04-22QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES) +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510186094.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In practical applications, existing bismuth vanadate (BiVO4) photocatalysts have problems such as fast photogenerated carrier recombination rate, small specific surface area, weak adsorption capacity and reduced stability due to photocorrosion.

Method used

Agriculture and forestry waste-derived biomass carbon is used as a support to construct a heterojunction composite photocatalyst with BiVO4, and is prepared by in-situ composite and hydrothermal methods to form a strong interfacial bonding structure to enhance photocatalytic activity and stability.

Benefits of technology

It significantly improves the photocatalytic activity and stability of the photocatalyst, can efficiently remove antibiotics in water, has a degradation rate of more than 70%, and maintains high efficiency in multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857478A_ABST
    Figure CN119857478A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth vanadate (BiVO4) / biomass charcoal composite photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of environmental functional materials. According to the catalyst, biomass charcoal generated by pyrolysis of reed straw is used as a carrier, and BiVO4 is loaded on the porous surface of the biomass charcoal through an in-situ hydrothermal method, so that a heterojunction structure is formed. According to the composite material, norfloxacin is enriched through the high adsorption performance of the biomass charcoal, separation of photon-generated carriers is promoted through heterojunction of BiVO4 and the biomass charcoal, the catalytic activity under visible light is remarkably improved, the degradation efficiency of norfloxacin can reach 88% within 180 min, and after four times of circulation, the composite material shows good circulation stability. The method has the advantages of low cost, resource utilization and high stability, and a green solution is provided for antibiotic pollution control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental functional materials, and specifically relates to a visible light responsive bismuth vanadate (BiVO 4 ) and biomass carbon composite photocatalyst and its application in degrading antibiotics in water. Background Art

[0002] Antibiotics are important drugs in the medical and aquaculture fields. In recent years, the problem of antibiotic residues in water bodies has become increasingly serious. In natural water bodies, antibiotics can induce the production and migration of resistance genes, threatening ecological security and human health. Traditional water treatment technologies (such as biological methods, adsorption methods, and coagulation and sedimentation) have limited removal of trace antibiotics, and there is an urgent need to develop efficient, green, and sustainable antibiotic deep treatment technologies.

[0003] Photocatalytic technology uses semiconductor materials to produce active species under light, which can directly oxidize and decompose antibiotics, and has the advantages of being green and low in energy consumption. 4 ) As a semiconductor material that responds to visible light, it still faces the following challenges in practical application: fast recombination rate of photogenerated carriers; small specific surface area and weak adsorption capacity for pollutants; photocorrosion phenomenon during long-term use leads to decreased stability. Biochar has a high specific surface area, rich pore structure and surface functional groups, and can be used as a carrier of semiconductor materials to construct a composite synergistic system. 4 Composite with biochar can improve the photocatalytic performance, but it is easy to lead to uncontrollable pore structure and surface chemical properties similar to BiVO 4 Problems such as poor compatibility. Summary of the invention

[0004] In order to solve the above problems, the present invention proposes to use biochar derived from agricultural and forestry waste as a carrier and 4 A heterojunction composite photocatalyst is constructed and applied to the degradation and removal of antibiotics to synergistically improve the photocatalytic activity and stability. Specifically, the technical solution provided by the present invention is as follows:

[0005] In a first aspect of the present invention, there is provided a reed biomass charcoal / bismuth vanadate (BiVO 4 ) A method for preparing a composite photocatalytic material, the specific steps are as follows:

[0006] S1、BiVO 4 Synthesis: Bismuth nitrate (Bi(NO 3 ) 3 ·5H 2 O) and ammonium metavanadate (NH 4 VO 3) was dissolved in dilute nitric acid (pH = 1-2), and stirred until completely dissolved; the mixed solution was transferred to a polytetrafluoroethylene-lined reactor, reacted at 100-180°C for 6-12 hours, and the precipitate was collected by centrifugation after natural cooling, washed with deionized water and ethanol three times in sequence, and dried in vacuum at 60°C;

[0007] S2, reed biochar: reed straw was washed, dried and crushed, heated to 500-800°C at 5°C / min under nitrogen and kept warm for 1-2 hours to pyrolyze to generate reed biochar (labeled as RBC); the pyrolyzed RBC was immersed in HNO 3 solution for 1 hour, centrifuged and washed to neutrality and dried;

[0008] S3, bismuth vanadate / biomass carbon composite photocatalyst: In situ composite, different mass fractions of RBC (10% to 30%) were dispersed in BiVO 4 The precursor solution was ultrasonically treated; the mixed solution was subjected to hydrothermal reaction (hydrothermal temperature 180°C, hydrothermal time 12 hours) to make BiVO 4 Nanoparticles were grown directly on the surface of RBCs; after centrifugal drying, a heterojunction structure with strong interfacial bonding was formed (labeled as BC).

[0009] Preferably, in S1, the hydrothermal temperature is 120° C. and 180° C., and the drying time is 6 hours and 12 hours.

[0010] Further preferably, in S1, the hydrothermal temperature is 180° C., and the drying time is 12 hours.

[0011] Preferably, in S2, the pyrolysis temperature is 700° C., and the pyrolysis time is 1 hour.

[0012] Preferably, in S3, the mass fraction of RBC is 10%, 20% and 30%.

[0013] In a second aspect of the present invention, a bismuth vanadate / biomass carbon composite photocatalyst is provided, which is prepared by the preparation method of the bismuth vanadate / biomass carbon composite photocatalyst described in any one of the above items.

[0014] The third aspect of the present invention provides an application of a bismuth vanadate / biochar composite photocatalyst, which comprises the following steps: adding a photocatalyst (15-30 mg) to 10 mg / L of norfloxacin to be treated wastewater and stirring sufficiently; initiating a photocatalytic oxidation reaction under visible light conditions; after stirring in the dark for 30 minutes, turning on the light source, and taking samples at regular intervals (0-180 minutes) to detect the concentration of norfloxacin.

[0015] Preferably, the sampling time intervals are 15 min, 30 min, 60 min, 120 min and 180 min.

[0016] The present invention has the following beneficial effects:

[0017] (1) The present invention uses reed straw as raw material, realizing waste resource utilization while effectively reducing the cost of material preparation;

[0018] (2) The bismuth vanadate / biomass carbon composite photocatalyst was prepared by in-situ composite. The heterojunction structure significantly blocked the photohole recombination and promoted the photogenerated electrons from BiVO 4 Migrate to RBC; In addition, the hydrothermal method adopted in the present invention has the advantages of low temperature, high efficiency, environmental protection, energy saving, simple equipment, etc.

[0019] (3) The present invention applies a composite photocatalyst to the degradation and removal of norfloxacin, which can efficiently generate oxygen-containing free radicals and achieve efficient and rapid removal of pollutants.

[0020] (4) Mechanical strength of RBC protects BiVO 4 Free from light corrosion, the degradation rate remains around 70% after 4 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 BiVO 4 XRD spectra of RBC and BC

[0022] Figure 2 BiVO 4 UV-visible diffuse reflectance spectra of BC

[0023] Figure 3 Removal efficiency of norfloxacin by different catalysts

[0024] Figure 4 Effect of BC dosage on the degradation of norfloxacin

[0025] Figure 5 Efficiency of BC cycle in degrading norfloxacin

[0026] Figure 6 XRD comparison of BC before and after degradation DETAILED DESCRIPTION

[0027] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0028] Example 1: This example provides a method for synthesizing bismuth vanadate, which specifically includes the following steps: bismuth nitrate (Bi(NO3 ) 3 ·5H 2 O) and ammonium metavanadate (NH 4 VO 3 ) was dissolved in dilute nitric acid (pH = 1-2) at a Bi:V molar ratio of 1:1, and stirred until completely dissolved; the mixed solution was transferred to a polytetrafluoroethylene-lined reactor, reacted at 100°C for 6 hours, and the precipitate was collected by centrifugation after natural cooling, washed with deionized water and ethanol for 3 times in sequence, and dried in vacuo at 60°C.

[0029] Example 2

[0030] This embodiment is basically the same as embodiment 1, except that the hydrothermal temperature is 120° C. and the hydrothermal time is 6 hours.

[0031] Example 2

[0032] This embodiment is basically the same as embodiment 1, except that the hydrothermal temperature is 140° C. and the hydrothermal time is 6 hours.

[0033] Example 3

[0034] This embodiment is basically the same as embodiment 1, except that the hydrothermal temperature is 160° C. and the hydrothermal time is 6 hours.

[0035] Example 4

[0036] This embodiment is basically the same as embodiment 1, except that the hydrothermal temperature is 180° C. and the hydrothermal time is 6 hours.

[0037] Example 5

[0038] This embodiment is basically the same as embodiment 1, except that the hydrothermal temperature is 180° C. and the hydrothermal time is 12 hours.

[0039] Example 6: This example provides a method for preparing reed biomass charcoal. Reed stalks are washed, dried, and crushed to a particle size of ≤1 mm. The temperature is raised to 500°C at 5°C / min under nitrogen and kept warm for 1 hour to pyrolyze and generate reed biomass charcoal. The pyrolyzed RBC is immersed in HNO 3 The solution was kept for 1 hour, centrifuged and washed to neutrality and dried.

[0040] Example 7

[0041] This embodiment is basically the same as embodiment 5, except that the pyrolysis temperature is 500° C. and the pyrolysis time is 2 hours.

[0042] Example 8

[0043] This embodiment is basically the same as embodiment 5, except that the pyrolysis temperature is 600° C. and the pyrolysis time is 1 hour.

[0044] Example 9

[0045] This embodiment is basically the same as embodiment 5, except that the pyrolysis temperature is 700° C. and the pyrolysis time is 1 hour (marked as RBC).

[0046] Example 10

[0047] This embodiment is basically the same as embodiment 5, except that the pyrolysis temperature is 800° C. and the pyrolysis time is 1 hour.

[0048] Example 11: This example provides a method for preparing a bismuth vanadate / biomass carbon composite photocatalyst, using in-situ compounding, dispersing 10% by mass fraction of RBC prepared in Example 9 in BiVO 4 The precursor solution was ultrasonically treated for 30 minutes; the mixed solution was subjected to a hydrothermal reaction (hydrothermal temperature of 180° C., hydrothermal time of 12 hours); after centrifugal drying, a bismuth vanadate / biomass carbon composite photocatalyst was obtained.

[0049] Comparative Example 1: This comparative example is basically the same as Example 11, except that the mass fraction of RBC is 20%.

[0050] Comparative Example 2: This comparative example is basically the same as Example 11, except that the mass fraction of RBC is 30%.

[0051] XRD spectra were analyzed for Example 5, Example 9 and Example 11 ( Figure 1 ), the results show that BiVO 4 The characteristic peaks of 28.75° are consistent with the mixed structure of monoclinic scheelite (JCPDS No.14-0688) and tetragonal zircon (JCPDS No.14-0133). 4 The (121) crystal plane of BiVO 4 The main structure of BiVO is monoclinic scheelite. 4 Due to the coupling effect with biochar, the characteristic peaks presented by BC also have a monoclinic scheelite structure.

[0052] UV-Vis diffuse reflectance spectroscopy analysis was performed on Example 5 and Example 11 ( Figure 2 ), the results show that the absorption edge of the bismuth vanadate / biomass carbon composite photocatalyst is from 510nm (pure BiVO 4 ) extended to 550nm, E gIt drops from 2.51eV to 2.46eV, which shows that the existence of heterojunction can improve the absorption efficiency of BC visible light and narrow the band gap.

[0053] Application Example 1: Using the catalysts synthesized in Example 5, Example 9, Example 11, Comparative Example 1 and Comparative Example 2, the degradation and removal of norfloxacin was performed. The specific steps are as follows: 25 mg of the catalyst was added to 10 mg / L of the wastewater to be treated with norfloxacin, and the mixture was stirred thoroughly; a photocatalytic oxidation reaction was initiated under visible light conditions; after stirring for 30 minutes in a dark environment, the light source was turned on, and samples were taken at 15 minutes, 30 minutes, 60 minutes, 120 minutes and 180 minutes, respectively, to detect the concentration of norfloxacin. The results are as follows: Figure 3 shown.

[0054] The results show that BiVO 4 Compared with RBC, the photocatalytic effect of BC has been greatly improved. The catalyst prepared in Example 2 has the highest photocatalytic performance, and the degradation rate of norfloxacin can reach 88%. The adsorption performance of the catalyst in Example 2 is significantly improved compared with that of the catalyst in Example 11 and Example 1. However, the excessive biochar hinders the transmission of light, resulting in a decrease in the photocatalytic performance of the catalyst prepared in Example 2.

[0055] Application Example 2: Using the catalyst prepared in Comparative Example 2, the degradation and removal of norfloxacin was performed. The specific steps are as follows: 15, 20, 25 and 30 mg of the catalyst were added to 10 mg / L of the wastewater to be treated with norfloxacin, and the mixture was stirred thoroughly; a photocatalytic oxidation reaction was initiated under visible light conditions; after stirring for 30 minutes in a dark environment, the light source was turned on, and samples were taken at 15 minutes, 30 minutes, 60 minutes, 120 minutes and 180 minutes, respectively, to detect the concentration of norfloxacin. The results are as follows: Figure 4 shown.

[0056] The results show that as the dosage of the catalyst prepared in Comparative Example 2 increases, the degradation efficiency of BC on norfloxacin gradually increases. The degradation efficiencies are 82.5%, 85%, 88% and 89% when the dosage increases from 15 mg to 30 mg, respectively. However, when the dosage increases from 25 mg to 30 mg, the increase in degradation efficiency is small. Considering the overall catalytic efficiency and cost, 25 mg is selected as the optimal dosage for degrading norfloxacin.

[0057] Application Example 3: Using the catalyst prepared in Comparative Example 2, a degradation and removal cycle test of norfloxacin was carried out. The specific steps are as follows: (1) Add 25 mg of the catalyst to 10 mg / L of the wastewater to be treated with norfloxacin and stir thoroughly; induce a photocatalytic oxidation reaction under visible light conditions; after stirring for 30 minutes in a dark environment, turn on the light source, take a sample after 180 minutes, and detect the concentration of norfloxacin; (2) Wash and dry the BC, repeat step (1), and detect the concentration of norfloxacin. The cycle is repeated 4 times in total. The results are as follows: Figure 5 The results show that after four cycles, the removal rate of BC for norfloxacin is about 70%, and it still has certain catalytic performance. Furthermore, the XRD spectra of BC before and after the cycle ( Figure 6 ) analysis, it was found that the crystal form of the material after the cycle changed less than that before the cycle, indicating that the material still has good stability after multiple cycles.

Claims

1. A method for preparing a bismuth vanadate (BiVO4) / biomass carbon composite photocatalyst, characterized in that: The preparation of the composite photocatalysis includes: synthesis of BiVO4, preparation of biomass carbon carrier and in-situ compounding of catalyst.

2. The catalyst in-situ compound according to claim 1, characterized in that: The BiVO4 precursor is subjected to a hydrothermal reaction with biomass charcoal to obtain the product.

3. The bismuth vanadate / biomass carbon composite photocatalyst according to claim 2, characterized in that: The mass fraction of the biomass charcoal is 10% to 30%.

4. The bismuth vanadate / biomass carbon composite photocatalyst according to claim 2, characterized in that: The hydrothermal temperature is 180° C. and the hydrothermal time is 12 hours.

5. The bismuth vanadate / biochar composite photocatalyst according to claim 2, characterized in that: The mixture after the hydrothermal reaction is centrifuged, washed and dried at one time; wherein the centrifugal speed is 1000 rpm and the centrifugal time is 10 min; the drying temperature is 70° C. and the drying time is 6 hours.

6. Use of the bismuth vanadate / biochar composite photocatalyst according to any one of claims 1 to 5 in photocatalytic degradation of norfloxacin, characterized in that: include: Adding the photocatalyst into the wastewater to be treated containing norfloxacin and stirring the mixture thoroughly; Photocatalytic oxidation reaction was induced under visible light conditions to remove norfloxacin from wastewater.

7. The application method according to claim 6, characterized in that: The initial norfloxacin concentration was 10 mg / L, and the dosage of the photocatalyst was 15-30 mg.

8. The application method according to claim 6, characterized in that: After being recycled for 4 times, the degradation rate of norfloxacin still remained at about 70%.

Citation Information

Cited By

  • Copper molybdate composite material, preparation method thereof and method for photodegrading levofloxacin hydrochloride

    CN121755219A